Improving the technique of prosthetic ventroplasty of the anterior abdominal wall - Sergey Vladimirovich Kapralov; Vladimir Vladimirovich Alipov; Maxim Andreyevich Polidanov; Ivan Evgenyevich Kondrashkin; Igor Sergeevich Blokhin; Islam Shamilovich Rasulov; Tamirlan Aslanovich Tirbulatov (Байкальский медицинский журнал, 2023)
Aim. Search for a more advanced technique for installing a mesh implant during ventroplasty of the anterior abdominal wall.Materials and methods. Modeling of prosthetic venteroplasty was carried out using laboratory animals - rabbits weighing 2000±50 g and rats weighing 400±50 g. As part of the experiment, implantation mesh material was used: "Prolene" and "REPEREN". Ventroplasty was performed using the following techniques: onlay, inlay and sublay. The implant was fixed with a continuous suture. On the 21st day of the experiment, the material was collected to study its biomechanical and morphological properties.Assessment of the morphological properties of preparations stained with hematoxylin-eosin and picrofuchsin according to Van Gieson was performed by histological methods. Biomechanical properties were evaluated using an INSTRON-5944 bursting machine.Results. In the course of comparing the biomechanical properties of the abdominal wall with the maximum value of load (H), stress (Mpa), and Young's modulus, the following results were obtained, a significantly significant dependence of the biomechanical and morphological properties of prosthetic ventroplasty on the mesh implant suturing technique was confirmed, and the advantages of sublay separation ventroplasty technology were scientifically substantiated.Conclusion. The experiment made it possible to confirm the dependence of biomechanical and morphological properties of prosthetic ventroplasty on the technique of mesh implant stitching used, to substantiate the advantages of separation ventroplasty using sublay technology.